1997
DOI: 10.1038/sj.bmt.1700799
|View full text |Cite
|
Sign up to set email alerts
|

CD34 positive PBPC expanded ex vivo may not provide durable engraftment following myeloablative chemoradiotherapy regimens

Abstract: Summary:suppression. Finally, culture conditions may be developed which could be applied to gene transduction protocols. We have previously demonstrated that CD34 + cells, Most investigators initiate stem/progenitor cell expansion selected from peripheral blood progenitor cells (PBPC), with CD34 + cells purified by positive selection since these can be expanded in ex vivo culture and can be infused cells appear to be superior to unselected material. In in tandem with unmanipulated PBPC with little or no additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(78 citation statements)
references
References 1 publication
4
74
0
Order By: Relevance
“…Williams et al 26 obtained substantial expansion of myeloid precursors in ex vivo bag cultures of CD34 + leukapheresis cells stimulated with PIXY and subsequent prompt neutrophil recovery in graft recipients. Using other stimulating factors, Holyoake et al 27 reported similar results for the early phase of hematopoietic recovery in four patients. However, further investigations will be necessary to demonstrate the capacity of these expanded cells to induce long-term engraftment in patients who have undergone true myeloablative conditioning.…”
Section: Discussionsupporting
confidence: 61%
“…Williams et al 26 obtained substantial expansion of myeloid precursors in ex vivo bag cultures of CD34 + leukapheresis cells stimulated with PIXY and subsequent prompt neutrophil recovery in graft recipients. Using other stimulating factors, Holyoake et al 27 reported similar results for the early phase of hematopoietic recovery in four patients. However, further investigations will be necessary to demonstrate the capacity of these expanded cells to induce long-term engraftment in patients who have undergone true myeloablative conditioning.…”
Section: Discussionsupporting
confidence: 61%
“…Current methods to ex vivo expand umbilical cord blood cells may introduce defects that lead to engraftment failures as has been reported using expanded 25 or transduced 29 autologous CD34 þ cells. Guenechea et al 30 transplanted fresh and ex vivo-expanded CD34 þ cord blood cells into irradiated non-obese diabetic (NOD)/SCID mice and while they found no differences in engraftment at 4 months, engraftment at 3 weeks was impaired when the expanded cells were used, suggesting that expanded cells might do not facilitate engraftment.…”
Section: Assessment Of Engraftmentmentioning
confidence: 99%
“…Stem cell assays to evaluate UCB expansion With the clinical failure of ex vivo expansion when the expanded product was used as the sole stem cell source 25 and the lack of improvement when the manipulated and unmanipulated products were both infused, 21,24 the current preclinical models and predictive assays for engraftment of all cell lineages deserve further development. Long-term engraftment is dependent upon the number and engraftment ability of the HSC transplanted; therefore, the ideal assay for this purpose must be simple, quantitative and reliably demonstrate engraftment capacity.…”
Section: Current Needs For Successful Hsc Expansionmentioning
confidence: 99%
“…Autologous progeny cells after culture/expansion in cytokine combination including IL-3 have been successfully infused into patients after a nonmyeloablative conditioning regimen [18]. In another study, when patients were given a myeloablative conditioning regimen, cells expanded in IL-3-containing cytokines failed to produce engraftment [19]. More recent data indicated that culture in IL-3 led to a decrease or loss of primitive hematopoietic cells with reconstitution potential [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%